Spectrophotometric Bivariate Method for Determination of Candesartan Cilexetil in Presence of its Alkaline Induced Degradation Product - Al-Arfaj, Nawal; Al-Onazi, Wedad; Al-Brashy, Amina (Asian Journal of Chemistry, 2012)
A simple, sensitive, selective and precise stability -indicating method for the determination of candesartan cilexetil in presence of its alkaline degradate and in tablets was developed and validated. The method is based on determination of candesartan cilexetil by the bivariate calibration depending on simple mathematic algorithm which provide simplicity and rapidity. The method showed good linearity in the range of 1- 12 μg mL-1 at 225 and 2-12 μg mL-1 at 250 nm with mean percentage recovery 100.29 ± 0.64. Candesartan cilexetil can be determined in the presence of up to 80 % of its alkaline degradate, the selectivity of the method was checked using laboratory prepared mixtures. The proposed method has been successfully applied to the analysis of candesartan cilexetil in bulk and in commercial tablets without interference from additives or excipients and the results were satisfactory compared with a reference method. Also, the suggested method was successfully applied to the content uniformity testing and degradation kinetic study.